Rebuilding After Displacement: Identifying the Needs of Displaced Communities from the Perspective of the Built Environment - Carmichael, Andrew; Liyanage, Champika; Villalba-Romero, Felix; Oni-Jimoh, Temi; Jayakody, Chathuranganee (Springer Nature, 2023)
This chapter identifies the needs of internationally displaced communities in the United Kingdom (UK) within the past decade (2009–2019), in the context of the built environment. The chapter is based on the findings of qualitative analysis of interviews with experts working with the displaced in the UK. The interviewees were from different groups responsible for managing different aspects of the refugee experience. Research results reveal that the UK government’s standards vary across the range of different categories of displaced persons.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Catástrofes - Aspectos económicos; Víctimas de catástrofes; Built environment; Displaced communities; Economic and social needs; Integration; Resettlement; United Kingdom